Influence of Substituted Elements on Reflection Loss of Ba-Ferrite Nanoparticle - Yang S.; Jeong K.-Pil.; Park S.-Y.; Kim J.-Gon. (Archives of Metallurgy and Materials, 2017)
Due to the rapid development of the information communication industries, it is expected that next-generation mobile communication devices in the data communication environment will be used at the same time in the L~X band (1–12 GHz). To mutual electric wave interference prevention, research on wave absorbers in L~X band is needed. In this paper, barium ferrite was researched as L~X band wave absorber. The Barium ferrite (BaM, Ba ferrite) substituted by divalent ions (Co2+, Cu2+, Ni2+, Zn2+) and tetravalent ion (Ti4+). The substituted Ba ferrite nanoparticles were fabricated by sol-gel process. Lattice parameter, particle size, magnetic properties, and reflection loss were analyzed by X-ray diffraction (X-RD), a Vibrating Sample Magnetometer (VSM), and a Network Analyzer. Lattice parameter of Ba ferrite was changed 0.0005 to 0.0078 Å in a-b direction, and 0.0187 to 0.0445 Å in c-direction by substituted elements, and it influenced on magnetic anisotropy. In addition, Co-Ti substitution elements influenced that coercive force decrease 5,739 to 2,240 Oe. Moreover, reflection loss frequencies were shifted from 16.3 GHz to 14.4 and 17.4 GHz by substituted elements Co-Ti and Zn-Ti.